Fenomena Doom Spending (Perilaku Konsumtif) di Kalangan Remaja : Kajian dari Teori Schacter - Singer - Mardhatilla, Nadia (HUMANIKA, 2025)
The phenomenon of doom spending among adolescents has emerged as an emotional response to anxiety, social-digital pressures, and economic uncertainty, exacerbated by easy financial access and doomscrolling culture. This study aims to analyze how emotional, social, and digital processes shape doom spending behavior and to formulate preventive interventions to mitigate it. Utilizing Schachter–Singer’s two-factor theory of emotion and the concept of emotional regulation, this research employs a qualitative phenomenological method based on a literature study through thematic and conceptual analysis. The findings indicate that doom spending is a maladaptive coping mechanism where physiological stress from exposure to negative content is cognitively mislabeled, leading to shopping being perceived as an instant solution for dopamine release. Adolescents are the most vulnerable group due to immature self-control and external pressures such as FOMO, the YOLO norm, flexing culture, and social media algorithms. This behavior is characterized by impulsive purchases that often result in post-consumption regret. To address this phenomenon, strategic interventions are required, including emotional education through mindfulness techniques, enhanced digital financial literacy, and the reinforcement of spiritual values and simple living. By integrating emotional control and a clear distinction between needs and wants, adolescents can build stronger emotional resilience and healthier consumption patterns amidst the uncertainties of the digital era.